A case study on the effectiveness of "Sakitalis" suspension for extraction - Dela Cruz, Arlene W.; Pacete, Kristine Rachelle R.; Tumang, Heherson (Adviser).
The different fields of dentistry have witnessed many significant technological advances through the years. In the Philippines however, these advances are few and far between and are most commonly beyond the reach of the average citizen. Along the streets of Quiapo, a yellowish suspension is peddled for sale. The suspension is called "sakitalis" alluding to its ability to remove pain. Among its many claims is its ability for extractions that are painless and use minimal force. It is the aim of this case study to test the effectiveness of the "sakitalis" suspension in extracting teeth in-vivo. This was done through an experimental extraction procedure involving a 5-year old Chihuahua dog. Pre-operative conditions were determined and recorded. A cotton pellet was then soaked with the "sakitalis" suspension and applied to the free gingiva and mucosa surrounding the lower left corner incisor. Afterwhich, the tooth was luxated from labial to lingual with the use of a toothpick and appropriate finger pressure. When the tooth was adequately loose, it was removed from the socket with the use of a mosquito hemostat. The socket was then plugged with a cotton pellet and allowed to stay for 1 minute. Immediate results showed that there was a change in tooth mobility from degree 2 to 3, the tooth was removed from its socket, there was no immediate post-operative bleeding and there were no post-operative complications. However, results of phytochemical screening proved negative. The results were able to show, categorically, that the "sakitalis" suspension is effective in extracting teeth and was thus, able to bring about the successful extraction of the lower left corner incisor of the test subject. It is thus evident that the explanation of the experiment results remain unclear and the outcome of consequent procedures are uncertain.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.